TIME-DEPENDENT SORPTION OF CD2+ ON CAX ZEOLITE: EXPERIMENTAL OBSERVATIONS AND MODEL PREDICTIONS - Ahmed I.A.M.; Young S.D.; Crout N.M.J. (My University, 2006)
Sorption, fixation and desorption kinetics of Cd2+ on calcium-exchanged zeolite-X were studied using an isotopic dilution technique utilizing 109Cd. The technique provided reliable measurements of time-dependent fixation of Cd and was validated using chabazite, which demonstrated wholly reversible Cd2+ ion exchange. A first-order kinetic model was developed to describe the progressive transfer of Cd2+ to a less reactive form in X-zeolite, following initial sorption, and subsequent desorption of Cd subject to different initial contact times. The kinetic model differentiates between two 'pools' of sorbed Cd2+ on zeolite-X, designated labile and non-labile sorbed Cd in which the labile sorbed Cd is in immediate equilibrium with the free Cd2+ ion activity in solution. Additionally, an intra-particle diffusion model was developed and compared with the kinetic model to determine whether time-dependent Cd sorption is controlled by reaction kinetics or diffusion within zeolite particles. The kinetic model provided a much better fit to the experimental data (R2 = 0.987) than the diffusion model. The rate constants describing Cd dynamics in CaX zeolite gave a half-time for Cd desorption of ~77 d, for release to a 'zero-sink'. © 2006 Elsevier Inc. All rights reserved.